Komparasi Zakat Profesi dalam Agama Islam dan Persepuluhan dalam Agama Kristen Protestan - Gin Gin Muhamad Ridwan (Jurnal Penelitian Ilmu Ushuluddin, 2021)
This study aims to discuss the similarities and differences between professional zakat in Islam and tithing in Christianity. This research method is a qualitative type through library research and field studies by applying comparative descriptive analysis. The results and discussion of this study indicate that professional zakat in Islam and tithing in Christianity both originate from the holy books of each religion, it is found that there are similarities and differences between professional zakat in Islam and tithing in Christianity, and the meeting point of both has implications for the development of religious philanthropy in Indonesia. This study concludes that tithing is required in Malachi 3:10-11 and professional zakat is required in QS al-Baqarah verse 267 where the wisdom of both is for the benefit of the people or congregation, while the difference is that tithing can be carried out by anyone and professional zakat can only be implemented by people who have reached nishab, and the first aims to return God's gift and the second aims to clean up wealth.